228k views
5 votes
10(x+3)-(-9x-4)= x-5 +3

User Surfi
by
5.9k points

2 Answers

7 votes

Answer:

Explanation:

Simplifying

10(x + 3) + -1(-9x + -4) = x + -5 + 3

Reorder the terms:

10(3 + x) + -1(-9x + -4) = x + -5 + 3

(3 * 10 + x * 10) + -1(-9x + -4) = x + -5 + 3

(30 + 10x) + -1(-9x + -4) = x + -5 + 3

Reorder the terms:

30 + 10x + -1(-4 + -9x) = x + -5 + 3

30 + 10x + (-4 * -1 + -9x * -1) = x + -5 + 3

30 + 10x + (4 + 9x) = x + -5 + 3

Reorder the terms:

30 + 4 + 10x + 9x = x + -5 + 3

Combine like terms: 30 + 4 = 34

34 + 10x + 9x = x + -5 + 3

Combine like terms: 10x + 9x = 19x

34 + 19x = x + -5 + 3

Reorder the terms:

34 + 19x = -5 + 3 + x

Combine like terms: -5 + 3 = -2

34 + 19x = -2 + x

Solving

34 + 19x = -2 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.

34 + 19x + -1x = -2 + x + -1x

Combine like terms: 19x + -1x = 18x

34 + 18x = -2 + x + -1x

Combine like terms: x + -1x = 0

34 + 18x = -2 + 0

34 + 18x = -2

Add '-34' to each side of the equation.

34 + -34 + 18x = -2 + -34

Combine like terms: 34 + -34 = 0

0 + 18x = -2 + -34

18x = -2 + -34

Combine like terms: -2 + -34 = -36

18x = -36

Divide each side by '18'.

x = -2

Simplifying

x = -2

User Peter Bons
by
6.1k points
3 votes

Explanation:

10(x+3)-(-9x-4)=x-5+3

10x+30+9x+4=x-2

10x+9x+30+4=x-2

19x+34=x-2

19x-x=-34-2

18x=-36

x=-36/18

x=-2

User Matt Tenenbaum
by
5.9k points